Rational use of medicine in dentistry: do dentists prescribe antibiotics in appropriate indications? - AKICI, AHMET (SPRINGER HEIDELBERG, 2017)
There are concerns regarding appropriate use of antibiotics in dentistry practice. Data on dental antibiotic prescribing patterns by dentists is relatively limited. This nationwide study aimed to examine dentists' antibiotic prescriptions in a diagnosis-based manner in Turkey. This retrospective study on utilization of systemic antibiotics for dental problems was based on the national health data of the dentists obtained from Prescription Information System between January 2013 and August 2015. Only those prescriptions containing single diagnosis and at least one systemic antibiotic were included in the study. Antibiotic prescribing was compared by diagnoses and expertise of dentists. A total of 9,293,410 antibiotics were detected in 9,214,956 prescriptions that contained single diagnosis and at least one antibiotic. The number of antibiotics per prescription was 1.01. Periapical abscess without sinus (28.1%), dental examination (20.7%), and dental caries (16.2%) were the three most common indications in which antibiotics were prescribed by dentists. While only 3.4% of antibiotics were prescribed upon the single and appropriate cellulitis and abscess of mouth diagnosis, the remaining 96.6% was prescribed for irrational/uncertain indications. Consistent in all diagnoses, amoxicillin + enzyme inhibitor (58.6%) was the mainly prescribed antibiotic. Analysis of the most preferred amoxicillin + enzyme inhibitor prescriptions by expertise of dentists showed significantly much higher prescription rates among Group A specialists and Group B specialists (67.0 and 67.8%, respectively) than those in unidentified dental practitioners (58.2%, p < 0.0001). This study showed that dentists prescribed antibiotics in an arbitrary and mostly unnecessary manner. In general, their antibiotic choices for examined diagnoses could be regarded as irrational. These results indicate the urgent need for improvement of rational antibiotic prescribing habits of dentists.
Keywords: Rational pharmacotherapy; Dentistry; Dental indications; Antibiotic prescribing; CROSS-NATIONAL DATABASE; GENERAL DENTAL PRACTICE; RESISTANCE; CONSUMPTION; EUROPE